Florida: Data processing services not subject to tax (State tax review, 1993)
In the First Federal Savings and Loan Association of Putnam County case, the Florida Division of Administrative Hearings ruled that bookkeeping and data processing services provided to a full-service savings and loan institution were exempt from Florida sales tax as professional services.